Electromagnetic properties of LaCa[3]Fe[5]O[12] in the microwave range; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Golenkina V. V.; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Suslyaev V. I.; Korovin E. Yu.; Kuleshov G. E.; Kaykenov D. A.; Mustafin E. S.; Mylnikova T. S. Tatyana Stepanovna (2016, 2016)
Title screen